International spillovers in global asset markets - Ansgar Belke; Irina Dubova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The paper estimates the financial transmission between bond and equity markets within and between across the four largest global financial markets - the United States, the Euro area, Japan, and the United Kingdom. In a globalized world, where the complex transmission process across various financial assets is not restricted to just domestic market, we argue that international bond and equity markets are highly interconnected both within and across asset classes.
Keywords: E52; E58; F42; 330